Preheating of Gelatin Improves its Printability with Transglutaminase in Direct Ink Writing 3D Printing - Tan, Justin Jia Yao (Int J Bioprint, 2020)
Gelatin and transglutaminase (TG) ink is increasingly popular in direct ink writing three-dimensional (3D) printing of cellular scaffolds and edible materials. The use of enzymes to crosslink gelatin chains removes the needs for toxic crosslinkers and bypasses undesired side reactions due to the specificity of the enzymes. However, their application in 3D printing remains challenging primarily due to the rapid crosslinking that leads to the short duration of printable time. In this work, we propose the use of gelatin preheated for 7 days to extend the duration of the printing time of the gelatin ink. We first determined the stiffness of freshly prepared gelatin (FG) and preheated gelatin (PG) (5 – 20% w/w) containing 5% w/w TG. We selected gelatin hydrogels made from 7.5% w/w FG and 10% w/w PG that yielded similar stiffness for subsequent studies to determine the duration of the printable time. PG inks exhibited longer time required for gelation and a smaller increase in viscosity with time than FG inks of similar stiffness. Our study suggested the advantage to preheat gelatin to enhance the printability of the ink, which is essential for extrusion-based bioprinting and food printing.